A Whey Protein Hydrolysate Promotes Insulinotropic Activity in a Clonal Pancreatic β-Cell Line and Enhances Glycemic Function in ob/ob Mice - Gaudel, Celine; Nongonierma, Alice; Maher, Samuel; Flynn, Sarah; Krause, Mauricio; Murray, Brian; Kelly, Phillip; Baird, Alan; FitzGerald, Richard; Newsholme, Philip (American Society for Nutritional Sciences, 2013)
Whey protein hydrolysates (WPHs) represent novel antidiabetic agents that affect glycemia in animals and humans, but little is known about their insulinotropic effects. The effects of a WPH were analyzed in vitro on acute glucose-induced insulin secretion in pancreatic BRIN-BD11 β cells. WPH permeability across Caco-2 cell monolayers was determined in a 2-tiered intestinal model. WPH effects on insulin resistance were studied in vivo following an 8-wk oral ingestion (100mg/kg body weight) by ob/ob (OB-WPH) and wild-type mice (WT-WPH) compared with vehicle control (OB and WT groups) usinga 2 3 2 factorial design, genotype 3 treatment. BRIN-BD11 cells showed a robust and reproducible dose-dependent insulinotropic effect of WPH (from 0.01 to 5.00 g/L). WPH bioactive constituents were permeable across Caco-2 cell monolayers. In the OB-WPH and WT-WPH groups, WPH administration improved glucose clearance after a glucose challenge (2 g/kg body weight), as indicated by differences in the area under curves (AUCs) (P ≤ 0.05). The basal plasma glucose concentration was not affected by WPH treatment in either genotype. The plasma insulin concentration was lower in the OB-WPH than in the OB group (P ≤ 0.005) but was similar between the WT and WT-WPH groups; the interaction genotype 3 treatment was significant (P ≤ 0.005). Insulin release from pancreatic islets isolated from the OB-WPH group was greater (P ≤ 0.005) than that from the OB group but did not differ between the WT-WPH and WT groups; the interaction genotype 3 treatment was not significant. In conclusion, an 8-wk oral administration of WPH improved blood glucose clearance, reduced hyperinsulinemia, and restored the pancreatic islet capacity to secrete insulin in response to glucosein ob/ob mice. Hence, it may be useful in diabetes management.